The Ability of Supplying the Elliptical Items Omitted From a Written Text and its Impact on the Reading Comprehension of 4th Year Libyan University Students Studying EFL - Annajeh , Abdussalam A. (Journal of Education and Vocational Research, 2013)
This paper investigates the ability of supplying the elliptical items omitted from a written text and its impact on the reading comprehension of Libyan university students studying EFL. Ellipsis can be defined as the omission of one or more lexical items that are understood in the context, but which are required to make the sentence or utterance grammatically correct. An elliptical item could be nominal, verbal or clausal. 4th year English Department students from the English Department- Faculty of ArtsGharian in Al-Jabal Al-Gharbi University completed reading comprehension test. Seventy one out of a hundred and four students accepted to participate in the study. The test was modified to include many elliptical items and the students were asked to supply them. The results, which were statistically analyzed, suggested that the study participants were not able to supply the correct elliptical items and consequently had poor reading comprehension results. The mean marks achieved were only 33.8. This result may have many pedagogical implications.